2010
DOI: 10.1530/eje-09-0957
|View full text |Cite
|
Sign up to set email alerts
|

Long-term morphological, hormonal, and clinical follow-up in a single unit on 118 patients with adrenal incidentalomas

Abstract: Objective: To evaluate long-term morphological, functional, and clinical outcome in adrenal incidentalomas. Design and methods: A total of 118 patients (77 F and 47 M; age 62.3G1.0 years) with adrenal incidentalomas were evaluated at baseline and followed-up for median 3 years (range 1-10 years) by clinical, biochemical, hormonal, and morphological evaluation. Among them, six patients with diagnosis of subclinical Cushing's syndrome (SCS) underwent surgery. Results: At entry, 86% (nZ102) of tumors were nonfunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 37 publications
5
63
1
3
Order By: Relevance
“…Several studies have reported that hypertension improved after adrenalectomy in SCS patients, 8,[11][12][13] whereas some studies have shown that adrenalectomy did not significantly improve the CVD risk profile. 26,27 The present study, however, showed that not only hypertension but also DM/IGT and dyslipidemia significantly improved in our SCS patients after the removal of adrenal tumors. Our data are in accordance with those of a recent study showing that blood pressure, weight and fasting glucose in SCS patients improved after adrenalectomy.…”
Section: Discussioncontrasting
confidence: 58%
“…Several studies have reported that hypertension improved after adrenalectomy in SCS patients, 8,[11][12][13] whereas some studies have shown that adrenalectomy did not significantly improve the CVD risk profile. 26,27 The present study, however, showed that not only hypertension but also DM/IGT and dyslipidemia significantly improved in our SCS patients after the removal of adrenal tumors. Our data are in accordance with those of a recent study showing that blood pressure, weight and fasting glucose in SCS patients improved after adrenalectomy.…”
Section: Discussioncontrasting
confidence: 58%
“…In total, 12 studies were included: 7 cross-sectional studies (38,42,43,45,141,142,143) and 5 cohort studies (40,46,144,145,146). In eight studies, a comparison was made between patients with elevated (group 1) or normal (group 2) cortisol levels after a 1 mg dexamethasone test.…”
Section: Assessment Of Autonomous Cortisol Secretion In Relation To Cmentioning
confidence: 99%
“…The search yielded 854 references for abstract screening of which 26 studies (19,20,21,22,23,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49) were included in this systematic review (Fig. 1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…However, studies attempting to investigate the beneficial effect of adrenalectomy on cardiovascular risk factors in patients with SCS are characterized by small sample sizes and have generated inconsistent results. Although several authors reported various degrees of improvement in metabolic parameters (19,20,21), others showed no significant metabolic effect of adrenalectomy (22,23) in patients with autonomous glucocorticoid production.…”
mentioning
confidence: 99%